Preparation of nanoparticles from atmospheric pressure plasma jet-activated gas modified pectin for oral insulin delivery - Chen N; Zhang X; Cao W; Tian H; Hua X (Elsevier B.V., 2026)
This study investigates the effects of atmospheric pressure plasma jet-activated gas (APPJ) treatment on pectin and its nanoparticles (APPJ-pectin NPs), and explores their applications in oral insulin delivery systems. The results showed that as APPJ treatment progressed, the molecular weight of pectin significantly decreased, while the degree of esterification increased and its hydrophilic/hydrophobic properties altered. The insulin encapsulation efficiency of APPJ-pectin NPs exhibited minimal variation during the initial stage of treatment. In vitro release studies showed that APPJ-pectin NPs protected insulin in simulated gastric fluid and gradually released it at neutral pH, with the release rate initially decreasing and then increasing with extended APPJ treatment. The hemolysis rates of all samples ranged from 2% to 5%, suggesting that APPJ-pectin NPs exhibited favorable hemocompatibility. APPJ-pectin NPs primarily underwent transepithelial transport via the transcellular pathway, being internalized by endocytosis and subsequently transported intracellularly into the bloodstream. The transepithelial transport efficiency of APPJ-pectin NPs was evaluated using the Transwell system. APPJ treatment significantly increased the transport efficiency, with A60-NPs showing a 57.14% increase compared to the control. Confocal laser scanning microscope observations and flow cytometry experiments further confirmed this result, demonstrating that the uptake of APPJ-pectin NPs by Caco-2 cells was time-dependent, with A60-NPs exhibiting the highest uptake efficiency.
Keywords: Pectin; Atmospheric pressure plasma jet-activated gas; Nanoparticles; Oral insulin delivery; Transepithelial transport